ISOLASI DAN IDENTIFIKASI WABAH AVIAN INFLUENZA PADA BULAN OKTOBER 2004-MARET 2005 DI INDONESIA - Dharmayanti, NLP. I.; Indriani, R.; Damayanti, R.; Wiyono, A. (JURNAL BIOLOGI INDONESIA, 2005)
ABSTRACTIsolation and Identification of Avian Influenza Outbreak in October 2004 - March 2005in Indonesia. Recent outbreak of avian influenza A (HSNI) in poultry throughout Asiaincluding Indonesia caused major economic problems. Bird's infection with this virus wasidentified in Indonesia in January 2004. Since March 2004, the avian influenza cases hasdecreased, but then in October 2004 was reported that outbreak has occurred in some districtin Indonesia. This study is the first to isolation and identification the avian influenza outbreakin Indonesia in October 2004 until March 2005. Our finding revealed that outbreak of poultrydisease in this period was caused by an avian influenza H5 subtype.Keywords: Identification, virus avian influenza subtype H5